2021
DOI: 10.3390/agronomy11020196
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Growth and Inflorescence Initiation by Exogenous Gibberellic Acid3 and 6-Benzylaminopurine Application in Phalaenopsis Orchids

Abstract: This study was conducted to observe the effects of exogenous gibberellic acid3 (GA3) and 6-benzylaminopurine (BAP) treatments on the growth and inflorescence initiation of Phalaenopsis and to determine whether hormonal applications can substitute for low-temperature exposure for floral transition. Phalaenopsis Queen Beer ‘Mantefon’ clones were treated with no hormones (control), GA3 100 mg/L, GA3 200 mg/L, BAP 100 mg/L, and GA3 100 mg/L + BAP 100 mg/L by foliar spray. The treatments were carried at 28 °C for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Plant growth regulators will not be completely mobile if they are not sprayed directly on the leaf attached to the plant 73 . If only a single treated leaf remains green while other leaves abscise, assimilates will preferably translocate to the tissues treated with plant growth regulators and accumulate 74 . It is hypothesized that the hormone leads to assimilate translocation by establishing a new source-sink relationship 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth regulators will not be completely mobile if they are not sprayed directly on the leaf attached to the plant 73 . If only a single treated leaf remains green while other leaves abscise, assimilates will preferably translocate to the tissues treated with plant growth regulators and accumulate 74 . It is hypothesized that the hormone leads to assimilate translocation by establishing a new source-sink relationship 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Monopodial orchids, such as Phalaenopsis , have an apical meristem that remains active indefinitely while the bud primordia, which are capable of developing inflorescences, are formed in the axil of each leaf. Two or three inflorescences can be expected from the leaf axil under a 6-benzylaminopurine (6-BA) hormone treatment [ 25 ]. In sympodial orchids, such as Paphiopedilum , a new shoot may arise from the base of the previous shoot and differentiation of the flower bud primordium is directly associated with every new shoot [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…For orchid plants, the impact of GA 3 varies among species. For example, applied alone, exogenous GA 3 negligibly affected flower induction in Phalaenopsis [ 25 ]. Nevertheless, an injection of optimum levels of GA 3 can break flower bud dormancy under high temperature and promote the continuous development of inflorescences [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Burhan (2017) reported that spraying BAP 100 and 200 mg l -1 produced the largest pseudo-stem diameter, more new leaves and induced flowering in hybrid Dendrobium orchids. Lee et al (2021) showed that spraying BAP 100 mg l -1 on Phalaenopsis orchids increased leaf width, stem diameter, accelerated flowering and emergence of lateral bud growth. The three studies used high concentrations of BAP on various types of orchids.…”
Section: Introductionmentioning
confidence: 99%